Copper thin films on PET prepared at ambient temperature by ECR-CVD - Ko, H; Jhin, J; Byun, D; Lee, J; Park, D (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2005)
Metallized polymers were prepared at ambient temperature by an electron-cyclotron-resonance (ECR) chemical vapor deposition system equipped with (-)DC bias from the Cu(hfac)(2)-Ar-H-2 system. X-ray difraction (XRD) results showed that the Cu (111) peaks were clearly observed when H-2 was introduced to the plasma. The surface morphology showed that larger Cu grains were formed in the metal-organic composite films with the introduction of H-2 to the plasma. AES depth profiles showed that H-2 gas introduction to the plasma led to the formation of copper-rich films with a homogeneous composition. Also, the sheet resistance, was strongly dependent on the H2 content of the plasma. This means that hydrogen may lead to both the formation of stable volatile organic compounds and the reduction of copper, which influences both the crystallographic structure and the composition of films. As a result, crystalline copper films with a sheet resistance of 2-3 Omega(2) can be prepared on poly ethylene terephthalate with the addition of H-2 to the plasma.
Keywords: CHEMICAL-VAPOR-DEPOSITION; MICROWAVE PLASMA; GROWTH; ACETYLACETONATE; HEXAFLUOROACETYLACETONATE; METALLIZATION; PRESSURE; ENERGY; POWER